Positive psychology in practice - Linley, P. Alex (Hoboken, New Jersey John Wiley & Sons, Inc., 2004)
"Positive Psychology in Practice is an essential resource for understanding this new theory and applying its principles to all areas of professional practice."--Jacket.
The applied positive psychology perspective. Applied positive psychology : a new perspective for professional practice / P. Alex Linley and Stephen Joseph -- Historical and philosophical foundations. Positive psychology : historical, philosophical, and epistemological perspectives / Ingvild S. Jørgensen and Hilde Eileen Nafstad ; The good life, broadly and narrowly considered / Laura A. King, Jennifer Emilia Eels, and Chad M. Burton -- Values and choices in pursuit of the good life. The good life or the goods life? : positive psychology and personal well-being in the culture of consumption / Tim Kasser ; Value pathways to well-being : healthy values, valued goal attainment, and environmental congruence / Lilach Sagiv, Sonia Roccas, and Osnat Hazan -- Doing better but feeling worse : the paradox of choice / Barry Schwartz and Andrew Ward ; Fostering healthy self-regulation from within and without : a self-determination theory perspective / Kirk Warren Brown and Richard M. Ryan -- Lifestyle practices for health and well-being. Achieving sustainable new happiness : prospects, practices, and prescriptions / Kennon M. Sheldon and Sonja Lyubomirsky ; Physical activity : positive psychology in motion / Nanette Mutrie and Guy Faulkner ; Balancing time perspective in pursuit of optimal functioning in pursuit of optimal functioning / Ilong Boniwell and Philip G. Zimbardo -- Teaching and learning : methods and processes. Teaching students to make wise judgments : the "teaching for wisdom" program / Alina Reznitskaya and Robert J. Sternberg ; Introducing positive psychology to the introductory psychology student / Amy C. Fineburg ; Teaching positive psychology / Nick Baylis ; Rescuing our heroes : positive perspectives on upward comparisons in relationships, education, and work / Michael A. Cohn -- Positive psychology at work. Leading well ; transformational leadership and well-being / Niro Sivanathan [and others] ; Strengths-based development in practice / Timothy D. Hodges and Donald O. Clifton ; Positive and creative organization / Jane Henry ; Toward a positive psychology of executive coaching / Carol Kauffman and Anne Scoular -- Health psychology, clinical psychology, and psychotherapy : a positive psychological perspective. Positive psychology and health psychology : a fruitful liaison / Shelley E. Taylor and David K. Sherman ; Toward a positive clinical psychology : deconstructing the illness ideology and constructing an ideology of human strengths and potential / James E. Maddux, C.R. Snyder, and Shane J. Lopez ; The client : psychotherapy's missing link for promoting a positive psychology / Mark A. Hubble and Scott D. Miller ; Positive therapy : a positive psychological theory of therapeutic practice / Stephen Joseph and P. Alex Linley -- Positive psychology in the consulting room. Clinical applications of well-being therapy / Chiara Ruini and Giovanni A. Fava ; Strategies for accentuating hope / Shane J. Lopez [and others] ; A clinical approach to posttraumatic growth / Richard G. Tedeschi and Lawrence G. Calhoun ; Positive psychology and psychotherapy : an existential approach / Roger Bretherton and Roderick J. Ørner -- Strengths of character in practice. Classification and measurement of character strengths : implications for practice / Christopher Peterson and Nansook Park ; Emotional intelligence in practice / Peter Salovey, David Caruso, and John D. Mayer ; Gratitude in practice and the practice of gratitude / Giacomo Bono, Robert A. Emmons, and Michael E. McCullough ; Facilitating curiosity : a social and self-regulatory perspective for scientifically based interventions / Todd B. Kashdan and Frank D. Fincham ; Approaches to a good life : the emotional-motivational side to wisdom / Ute Kunzmann -- Positive development across the life span. Fostering the future : resilience theory and the practice of positive psychology / Tuppett M. Yates and Ann S. Masten ; Organized youth activities as contexts for positive development / Reed Larson [and others] ; Positive aging / George E. Vaillant -- Building community through integration and regeneration. Bringing subjectivity into focus : optimal experiences, life themes, and person-centered rehabilitation / Antonella Delle Fave and Fausto Massimini ; Good lives and the rehabilitation of offenders : a positive approach to sex offender treatment / Tony Ward and Ruth Mann ; Facilitating forgiveness : developing group and community interventions / Frank D. Fincham and Todd B. Kashdan -- Public policy initiatives : good governance and the good life. Human connections and the good life : balancing individuality and community in public policy / David G. Myers ; Happiness as a public policy aim : the greatest happiness principle / Ruut Veenhoven ; Findings on subjective well-being : applications to public policy, clinical interventions, and education / William Pavot and Ed Diener ; A population approach to positive psychology : the potential for population interventions to promote well-being and prevent disorder / Felicia A. Huppert -- Signposts for the practice of positive psychology. Toward a theoretical foundation for positive psychology in practice / P. Alex Linley and Stephen Joseph.
Includes bibliographical references and indexes.
Keywords: Positive psychology